2003
DOI: 10.1007/s00268-003-7054-0
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s Esophagus: Environmental Influences in the Progression of Dysplasia

Abstract: Barrett's esophagus (BE) is composed of multiple lineages including Paneth cells and endocrine cells in addition to gastric and intestinal cells. Although the origin of the BE stem cell is a matter of conjecture, the stem cells are clearly multipotent, and therefore the phenotype is restricted by genomic imprinting (termed restricted potency). Recent evidence suggests that the microenvironment may select various lineages. In this regard the proportion of gastric and specialized intestinal metaplastic cells has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Staining with Lendrum’s phloxine-tartrazine or immunohistochemical staining for lysozyme P did not confirm the presence of Paneth cells in the affected colon tissue (data not shown). It is tempting to speculate that these genes are indicative of the presence of metaplastic Paneth cells, which have been reported in both colonic CD and UC biopsies [36][38], whereas they are not found in healthy colon tissue [39], [40]. In patients these cells showed increased expression of human α-defensins DEFA5 and DEFA6 in the colon [22], [38], [41], [42].…”
Section: Discussionmentioning
confidence: 97%
“…Staining with Lendrum’s phloxine-tartrazine or immunohistochemical staining for lysozyme P did not confirm the presence of Paneth cells in the affected colon tissue (data not shown). It is tempting to speculate that these genes are indicative of the presence of metaplastic Paneth cells, which have been reported in both colonic CD and UC biopsies [36][38], whereas they are not found in healthy colon tissue [39], [40]. In patients these cells showed increased expression of human α-defensins DEFA5 and DEFA6 in the colon [22], [38], [41], [42].…”
Section: Discussionmentioning
confidence: 97%
“…Under normal, homeostatic conditions, Paneth cells are not found outside the small bowel, although they may appear ectopically in response to local inflammation throughout the gastrointestinal tract (22,23). Paneth cell numbers increase progressively throughout the small intestine, occurring at highest numbers in the distal ileum (24).…”
mentioning
confidence: 99%
“…19,20 Accumulating clinical and experimental studies suggest that the esophageal mucosal gland ducts harbor stem cells capable of differentiating into the columnar epithelium. [21][22][23][24] Detailed analysis of mitotic figures in the esophageal epithelium combined with immunohistochemical staining for proliferating cells has also demonstrated that cells in the flat interpapillary basal layer are candidates for esophageal epithelial stem cells. 25 There is also accumulating evidence that the squamous-to-columnar metaplastic sequence occurs through an intermediate, or transitional, phase characterized by the presence of an epithelium that shows combined squamous and columnar features, termed "multilayered epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…25 There is also accumulating evidence that the squamous-to-columnar metaplastic sequence occurs through an intermediate, or transitional, phase characterized by the presence of an epithelium that shows combined squamous and columnar features, termed "multilayered epithelium. [21][22][23][24][25][26] CDX2 is a nuclear transcription factor that has an important role in the early differentiation and maintenance of the intestinal epithelial phenotype. 27 CDX2 is specifically expressed in the small and large intestines and has been shown to activate other intestinal differentiation genes.…”
Section: Discussionmentioning
confidence: 99%